Sodium butyrate attenuates oxidative stress, apoptosis, and excessive mitophagy in sodium fluoride-induced hepatotoxicity in rats - Jing Xia; Xiaolin Zhang; Leiyu Xu; Nan Yan; Zhenxiang Sun; Xiaoxu Duan; Lu Meng; Rong Qi; Fu Ren; Zhengdong Wang (Ecotoxicology and Environmental Safety)
Aim: Long-term exposure to excess sodium fluoride (NaF) can cause chronic fluorosis. Liver, the most important detoxification organ, is the most vulnerable to the effects of fluoride. Sodium butyrate (NaB), a short-chain fatty acid produced in the intestinal tract, maintains normal mitochondrial function in vivo and reduces liver inflammation and oxidative stress. This study aims to investigate the protective effect and potential mechanism of NaB on liver injury in fluoride poisoned rats, particularly through the mitophagy pathway. Methods: Rats were randomly divided into four groups of 12 male rats each: control, NaF (100 mg/mL), NaB (1000 mg/kg), and NaF (100 mg/mL)+NaB (1000 mg/kg) group. Key findings: Changes in the levels of liver enzymes (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]) and antioxidant enzymes (superoxide dismutase [SOD], catalase [CAT], and malondialdehyde [MDA]) confirmed NaF-induced liver injury. NaF also changed the levels of autophagy markers (Beclin-1, LC3α/β, P62), and increased the level of apoptosis. The combined use of NaB and NaF significantly ameliorated these indices. Significance: These findings indicate that NaB may provide effective protection against NaF-induced liver injury through its attenuates oxidative stress, apoptosis, and excessive mitophagy mechanisms.